Looking Tasks Online: Utilizing Webcams to Collect Video Data from Home - Semmelmann, Kilian; Hönekopp, Astrid; Weigelt, Sarah (Frontiers in Psychology, 2017)
Online experimentation is emerging as a new methodology within classical data acquisition in psychology. It allows for easy, fast, broad, and cheap data conduction from the comfort of people’s homes. To add another method to the array of available tools, here we used recent developments in web technology to investigate the technical feasibility of online HTML5/JavaScript based video data recording. We employed a preferential looking task with children between 4 and 24 months. Parents and their children participated from home through a three-stage process: First, interested adults registered and took pictures through a webcam-based photo application. In the second step, we edited the pictures and integrated them into the design. Lastly, participants returned to the website and the video data acquisition took place through their webcam. In sum, we were able to create and employ the video recording application with participants as young as 4 months old. Quality-wise, no participant had to be removed due to the framerate or quality of videos and only 7% of data was excluded due to behavioral factors (lack of concentration). Results-wise, interrater reliability of rated looking side (left / right) showed a high agreement between raters, Fleiss’ Kappa, κ = .97, which can be translated to sufficient data quality for further analyses. With regard to on-/off-screen attention attribution, we found that children lost interest after about 10 seconds after trial onset using a static image presentation or 60 seconds total experimental time. Taken together, we were able to show that online video data recording is possible and viable for developmental psychology and beyond.